Understanding Socio-economic Dynamics Shaping Rural Settlement of Chaurideurali, Kavre, Nepal - Jha, Aakriti; Budhathoki, Belisha (Rural Development Journal, 2025)
This study explores the socio-economic dynamics shaping rural settlements in Chaurideurali, Kavre, Nepal. The main objective of this study is to understand the socio-economic factors of rural settlements in Chaurideurali. A mixed-methods approach was employed, combining quantitative and qualitative data collection techniques to provide a holistic understanding of the challenges and opportunities faced by the community. The discussion of the study highlights significant challenges: widespread poverty, a predominantly elderly population due to youth migration, low literacy rates, and reliance on traditional, low-yield agriculture. The study reveals that 55 percent of the surveyed population is female, reflecting male outmigration, while 51 percent are over 61 years old. Fragmented and infertile land limits agricultural productivity, contributing to economic vulnerability, with 48 percent of households earning less than NPR 10,000 per month. Also, cultural resilience remains strong, with deep-rooted Hindu and Buddhist traditions and community-led rituals fostering social bonds. However, these practices are evolving amidst economic pressures and environmental challenges, including climate change and unsustainable land use. This study provides a comprehensive understanding of the socio-economic conditions in Chaurideurali. It underscores the need for integrated, community-focused, and environmentally sustainable development initiatives to address poverty, reduce outmigration, and foster resilience in rural settlements.